Promoting gender equality in irrigation - Theis, Sophie; Passarelli, Simone; Bryan, Elizabeth; Lefore, Nicole; Deneke, Seblewongle; Nyamadi, Ben; Mlote, Sophia (International Food Policy Research Institute, 2016)
Small-scale irrigation is increasingly recognized as a key strategy for enhancing agricultural productivity and food security under growing climate uncertainty in Africa south of the Sahara. Rainfed production dominates the region, but governments and other stakeholders are increasing investments in irrigation. As these efforts are being rolled out, the gender implications of irrigation must be consid-ered to ensure that both men and women have the opportunity to adopt irrigation technologies and benefit from these investments.